Bubbles Acting as Micro End‐Effectors for Dexterous Manipulation and Sensing in Aqueous Environment - Zichen Xu; Qingsong Xu (Advanced Intelligent Systems)
Achieving safe robotic manipulation at the microscopic scale usually requires sophisticated equipment, imposing accessibility difficulty in practice. Inspired by tiny bubbles in nature, a new paradigm is proposed for achieving multifunctional manipulation and sensing using microbubbles for biological application in aqueous environments at low cost. Without demanding the expensive cost of fabrication devices, bubbles with various sizes are easy to generate in situ, which is enabled by bubble‐endowed interface interactions. It is demonstrated that bubbles acting as micro end‐effectors rapidly and adaptively realize dexterous manipulation of microobjects such as biological organisms and droplets. They can function as microgrippers to grasp microobjects based on interface interaction‐induced adhesion and act as soft micromanipulators to safely manipulate fragile objects. Moreover, the bubble micro end‐effector can sense and perceive the designated objects for contact measurement of microforces or surface textures at a microscopic scale via the shape changes of their ultrasoft structures. The reported method successfully integrates grasping, manipulation, and measurement functions in liquid using a single microbubble of less than 1 mm3 volume. These nondestructive functionalities showcase promising prospects for bubble‐based micro end‐effectors in biological manipulation and sensing applications.